Lược đồ logic đối xứng và ứng dụng. Phần II: Ứng dụng của lược đồ logic đối xứng - Vân, Phan Chí (Journal of Computer Science and Cybernetics, 2016)
In this paper author exposes the application of the logical symmetric scheme for the mathematical knowledge presentations: he establishes one concrete logical symmetric scheme to illustrate the effect of the deductive rules for proving and analysing the logical structures of one series of many certain mathematical statements. In addition he also introduces the project of the application of the logical symmetric scheme for the usual knowledge presentations.